1969
DOI: 10.1002/pssb.19690340135
|View full text |Cite
|
Sign up to set email alerts
|

Propriétés des alliages InSb1−xBix II. Absorption Optique

Abstract: A. ?I[. JEAX-LOCIS et al.: Propriktks des alliages InSbl-,Bi, (I[) 341 phys. stat. sol. 31, 341 (1969) Subject classification: 20.1; 13.1; 22.2.4 Centre National #Etudes des Te'ldcommunications, Issy-les-,~~oulineaux ( a ) et Institut Polytechnique de Mexico ( b ) Propribtbs des alliages InSbl,Bi, 11. Absorption optiquel) Par A. M. JEAN-LOUIS (a), B. AYRAULT (a) et J. VARGAS~) (b) Nons avons mesurk a diffkrentes ternpkratures, I'absorption optique d'alliages semiconducteurs lnSb1 -,Biz. Les corrections usnelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

1969
1969
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 4 publications
0
8
0
1
Order By: Relevance
“…InSbBi has been successfully used as infrared photodetectors with a cutoff wavelength at 10.6 µm [30]. The first synthesis of InSbBi bulk material was realized using Czochralski (CZ) method by Jean-Louis et al [15] in 1969. In 1981, Oe et al [21] reported the first MBE growth of InSbBi thin films with smooth surface.…”
Section: Insbbi and Quaternary Alloysmentioning
confidence: 99%
“…InSbBi has been successfully used as infrared photodetectors with a cutoff wavelength at 10.6 µm [30]. The first synthesis of InSbBi bulk material was realized using Czochralski (CZ) method by Jean-Louis et al [15] in 1969. In 1981, Oe et al [21] reported the first MBE growth of InSbBi thin films with smooth surface.…”
Section: Insbbi and Quaternary Alloysmentioning
confidence: 99%
“…Jean-Louis et al 3) grew bulk In-Sb 1Àx Bi x by Czochralski bulk growth techniques and found that up to 2.4% InBi can be incorporated under thermoequilibrium conditions. Oe et al 4) attempted to grow InSb 1Àx Bi x alloy by molecular beam epitaxy and confirmed that it can be epitaxially grown on InSb substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Nous avons effectue sur ces nouveaux matkriaux des experiences d'effet Hall [l] et d'absorption optique [2]. Nous en avons tire deux determinations independantes et concordantes de la bande interdite fondamentale EG(x) qui montrent : 1. conformement aux prbvisions une diminution tres rapide de EG(x) quand la concentration x de bismuth presente dans l'alliage augmente: ti 77 O K le taux de dbcroissance est voisin de 3,6 eV par mole de InBi ; 2. d'autre part, une diminution simultanBe du coefficient de temperature y = -dE,/dT de 3 meV/deg par mole de bismuth.…”
Section: Introductionunclassified